Effect Invesment and The Rate of Inflation to Economic Growth in Indonesia - Saparuddin M; Selly Yolanda; Karuniana Dianta Sebayang (Faculty of Economics and Business, University of Pasundan, 2015)
This study aims is to determine the influence of investment and the rate of inflation either partially or simultaneously to economic growth in Indonesia. This research was conducted in Indonesia using data quarterly for 9 years from 2005 to 2013. Types of data used are secondary data. The research method is using time series multiple regression method. The regression results showed that investment and inflation partially and simultaneosly has positive and significant effect on economic growth in Indonesia.